Analysis of Globular Cells in Corneal Nerve Vortex - Hao, Ran; Liu, Ziyuan; Chou, Yilin; Huang, Chen; Jing, Dalan; Wang, Haikun; Gao, Shuang; Li, Xuemin (Frontiers in Medicine, 2022)
Purpose: Less was known about globular cells which were a type of dendritic cells (DCs) in cornea. We aimed to investigate the morphological and distribution characteristics of globular cells in corneal vortex and their clinical correlations with ocular surface. Methods: Case records of patients who underwent in vivo confocal microscopy (IVCM) were evaluated retrospectively. The morphology and distribution features of globular cells in cornea nerve vortex and their co-existence status with Langerhans cells (LCs) were analyzed. Data of ocular surface symptoms and signs were collected and their correlations with globular cells distribution patterns and dendritic forms were performed. Dry eye patients without LCs were treated with preservative-free artificial tears, while patients with LCs were treated with artificial tears and fluoromethalone until the activated LCs disappeared. Results: A total of 836 eyes from 451 individuals were included. Three distribution patterns of globular cells in vortex were investigated, type 1 scattered globular cells (57.66%), type 2 large amounts of globular cells (≥ 50 cells) gathering in vortex and along some fixed vortex direction horizontally (13.52%) and type 3 no globular cells (28.83%). Their location and cell count altered slightly in the follow-ups but would not disappear. LCs could co-exist with globular cells and could fade after treatment. The type 2 distribution pattern was associated with older age (p=0.000) and higher upper eyelid Meiboscore (p=0.006). Dendritic globular cells had higher Meiboscore than non-dendritic forms. Conclusions: Globular cells had characteristic distribution patterns and biological features different from LCs. They were associated with long-term irritation of the meibomian gland dysfunction.